IMPLEMENTATION OF MONITORING AND INVESTIGATION RESULTS BY THE ROKAN HILIR REGENCY INSPECTORATE AUDITOR ON REGIONAL PROPERTY - Rahmadani, Wahyu; Ardiansah; Andrizal (JILPR Journal Indonesia Law and Policy Review, 2025)
The purpose of this study is to analyze the implementation of the monitoring and investigation results by the Inspectorate Auditor of Rokan Hilir Regency on regional-owned assets, to analyze the obstacles in the implementation, and to analyze the efforts made to overcome those obstacles. The method used is sociological legal research. Based on the research findings, it is known that the implementation of the monitoring and investigation results by the Inspectorate Auditor of Rokan Hilir Regency on regional-owned assets has not been running optimally. This is evident from the discrepancies between audit findings and the corrective actions taken by the relevant Regional Government Organizations (OPD). Although some corrective measures have been initiated—such as updating inventory data, re-labeling items, and organizing asset documentation—these efforts are not yet evenly implemented across all OPDs and are not fully in accordance with the provisions of asset management as regulated in the Regulation of the Minister of Home Affairs Number 47 of 2021 concerning Procedures for Bookkeeping, Inventory, and Reporting of Regional-Owned Assets. The obstacles in implementing the monitoring and investigation results include, first, from an administrative perspective, the presence of numerous assets without adequate supporting documents such as certificates, handover reports, or decisions determining the status of use. These assets frequently become recurring findings due to the lack of legal and physical verification. Second, from a technical perspective, some OPDs do not have dedicated personnel managing assets, resulting in the responsibility being handed to other staff members who lack relevant expertise. Third, challenges also arise from asset control by third parties. Efforts to overcome these obstacles include, first, reorganizing the asset documentation system and strengthening internal supervision.